Association of recently described adipokines with liver histology in biopsy‐proven non‐alcoholic fatty liver disease: a systematic review. (24th November 2015) - Bekaert, M.; Verhelst, X.; Geerts, A.; Lapauw, B.; Calders, P.
Summary: The prevalence of non‐alcoholic fatty liver disease (NAFLD) is rising, as is the prevalence of obesity and type 2 diabetes. It is increasingly recognized that an impaired pattern in adipokine secretion could play a pivotal role in the development of NAFLD. We performed a systematic review to evaluate the potential link between newly described adipokines and liver histology in biopsy‐proven NAFLD patients. A computerized literature search was performed in PubMed, EMBASE and Web of Science electronic databases. Thirty‐one cross‐sectional studies were included, resulting in a total of seven different investigated adipokines. Studies included in this review mainly had a good methodological quality. Most adipokines were suggested to be involved in the inflammatory response that develops within the context of NAFLD, either at hepatic or systemic level, and/or hepatic insulin resistance. Based on literature, clinical studies suggest that chemerin, resistin and adipocyte‐fatty‐acid‐binding protein potentially are involved in NAFLD pathogenesis and/or progression. However, major inconsistency still exists, and there is a high need for larger studies, together with the need of standardized assays to determine adipokine levels.